Hypoglycemic and hypolipidemic effects of two mangrove plants in a streptozotocininduced animal model of diabetes (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This study aims at evaluating the anti-diabetic, hypolipidemic, and pancreatic histopathological changes of Rhizophora mucronata and Avicennia marina.  Materials and Methods: The experimental rats were divided into eight groups (n = 15 each). Streptozotocin was used to induce diabetes. Daily oral administration of an aqueous extract from the leaves of R. mucronata and A. marina at 400 mg/kg BW, and a mixture of the two extracts for 6 weeks was assessed. The measurements of serum glucose, insulin, and lipid profile were carried out. Pancreatic specimens were collected from all groups and processed for pathological studies.  Results: The study revealed that the plant extracts restored the levels of diabetic markers and lipid profiles of diabetic rats, with no significant changes in non-diabetic ones. The extract of R. mucronata exhibited more promising anti-diabetic and hypolipidemic effects than A. marina singly or combined.  Conclusion: Leaf extracts from R. mucronata, singly or combined, and A. marina, induced a potent anti-diabetic and hypolipidemic potential in diabetic rats.J. Adv. Vet. Anim. Res., 7(3): 421-428, Sep 2020http://doi.org/10.5455/javar.2020.g437